18-F fluorodeoxyglucose positron emission tomography/computed tomography findings of bilateral primary fallopian tube carcinoma and metastasis to the uterus: a case report and literature review. Issue 8 (August 2022) - Dai, Na; Deng, Shengming; Yang, Yi; Sang, Shibiao
Existing literature on primary carcinoma of the fallopian tube is limited because of the rarity of this disease. We report a patient with intermittent vaginal bleeding and vaginal discharge who underwent transvaginal ultrasound, magnetic resonance imaging, and 18-F-fluorodeoxyglucose positron emission tomography/computed tomography (18-F FDG PET/CT) in our hospital. Ultrasound showed a bilateral fallopian tube mass and a uterine lesion. Magnetic resonance imaging revealed typical sausage-shaped bilateral adnexal masses, but overlooked a small lesion in the uterus in the initial diagnosis. FDG PET/CT findings not only showed bilateral fallopian tube masses and uterine lesions, but also ruled out distant metastasis. Postoperative pathology confirmed bilateral primary high-grade serous adenocarcinoma of the fallopian tube with implants in the uterus. These findings suggest that 18-F FDG PET/CT imaging could be a good approach for the diagnosis and staging of primary carcinoma of the fallopian tube.